Cartographie des changements de l’occupation du sol entre 1990 et 2002 dans le nord du Sénégal (Ferlo) à partir des images Landsat - Mamadou Adama Sarr (Cybergeo)
The aim of this study of a part of the catchment’s area of the Ferlo (between 14°50 and 16° latitude north and 17°50 and 12°50 longitude west) in the northern region of Senegal, is to determine the changes in vegetation cover from a diachronic analysis of the types of land cover. The study is based on the exploitation of data from Landsat images from November 1990 (sensor TM) and November 2002 (ETM+ sensor). The methodology used, in addition to the digital processing of the satellite images, is based on the recognition of objects from field work and in relation with files previously put together (map of land-cover).The mapping of spaces plants’ evolution reveals a limited modification of areas that are not cultivated with on one hand greater areas of savannah tree or shrubs and areas prone to flooding, and on the other hand, a reduction of cultivated areas, temporary water and pseudo shrub -steppe. However, the interpretation of results must take into account the rainfall (1990 experienced heavier rainfall than 2002 in terms of annual rainfall), and the crucial role of pastoral mobility in the spatial dynamics of land-use.